Rights and Obligations of Husband and Wife According to Islamic Law in Constructing Sakina Family - Muhammad Ikbal Ali (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2022)
This research aims to know the rights and obligations of husband and wife in building a sakinah family. The method used in this study is the library research method with a normative approach. The research results show that Husband and wife understand that the position of wife and husband in the household is the same, but have different rights and obligations, although on the other hand the community understands that the position of the wife in the family is under the husband, they understand this from the understanding of salaf fiqh which states that the wife must uphold high her husband with honor and glory. The concept of Islamic marriage teaches that the rights possessed by husband and wife are in balance with the obligations imposed on them, a husband or wife has balanced obligations. To realize a harmonious, sakinah and peaceful family, this can be done by fostering the appreciation of Islamic religious teachings, fostering mutual respect, fostering an attitude of efficient living, and fostering an introspective attitude of each husband and wife.